The Prevalence of Fetal Neural Abnormalities Detected By Ultrasonography in Southeast Part of Turkey - Özkur, Ayhan; Kervancıoğlu, Selim; Dikensoy, Ebru; Akçalı, Aylin; Kervancıoğlu, Reşat; Bayram, Metin (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: The aim of this study was to determine the prevalence of fetal neural abnormalities detected by prenatal ultrasonography in a university hospital in Turkey, and to review the points critical on the diagnosis of each fetal neural abnormality. STUDY DESING: This is a single center retrospective study. The prenatal ultrasonographic imaging of all the women referred to Department of Radiology of Gaziantep University Medical School, between January 2000 and March 2006, for fetal ultrasonography were reviewed. Fetal ultrasonographies were performed with high resolution sonography devices and all the fetal neural abnormalities were recorded. RESULTS: A total of 32 (0.85%) fetuses with neural abnormalities among 3782 fetal ultrasonographies were detected. Of these 32, six were also confirmed to have fetal neural abnormality by using fast obstetric magnetic resonance imaging. The identified fetal neural abnormalities were as follows: seven Chiari II (0,18%), one Chiari III (0,02%), three Meckel-Gruber syndrome (0,08%), eight anencephaly (0,21%), two schizencephaly (0,05%), two colpocephaly (0,05%), two choroid plexus cysts (0,05%), one arachnoid cyst (0,02%), two Dandy-Walker Malformation with occipital encephalocele (0,05%) and one thoracal meningomyelocele (0,02%). CONCLUSIONS: The results of this study showed that the overall prevalence of fetal neural abnormalities in the Department of Radiology in Gaziantep University is relevant to current medical literature. However, the prevalence of schizencephaly is remarkably higher than previously reported, which is thought to be due to high sensitivity of high resolution sonography devices used in this study.